Revisionary notes on the fungus-growing ant genus Mycetarotes Emery (Hymenoptera, Formicidae) - Mayhé-Nunes,Antonio José (2006)
Mycetarotes is a small genus of the exclusively Neotropical fungus-growing ants, that includes M. parallelus (Emery), M. senticosus Kempf, M. acutus Mayhé-Nunes and M. carinatus Mayhé-Nunes. We hereby revise historical and recent information regarding Mycetarotes species for the first time, providing an identification key to workers, diagnoses, synoptic illustrated redescriptions of the species, including those of sexuals when known, updates of distributional records, and nest pictures of M. carinatus and M. parallelus. We comment the taxonomy and phylogenetic relationships among Mycetarotes and related genera, and on their geographical distribution. The available biological information on the genus is summarized.